Strategy and history : essays on theory and practice - Gray, Colin S. (London : Routledge, 2006)
"A selection of Colin Gray's more important contributions to strategic debate, Strategy and History provides a unique perspective on the strategic history of the past thirty years. Written by a participant-observer of and in strategic controversies, the essays range widely over some hotly debated topics and address a number of issues which have contemporary relevance to strategists: the importance of history for strategic understanding today, the nature of strategy and why it is difficult to do well, the challenge of nuclear weapons, revolutions in military affairs, and arms control. Colin Gray argues strongly for the continuing significance of geography and culture and concludes by addressing the ethical assumptions which provide some useful guidance to the strategist. Ultimately the book shows how essential it is to maintain a strategic, means-ends perspective and defines strategy as a pragmatic activity. This book will be essential reading for all students of strategy, contemporary history and international relations."--BOOK JACKET.
Introduction : holding the strategy bridge -- 1. Across the nuclear divide -- strategic studies, past and present [1977] -- 2. New directions for strategic studies? : how can theory help practice? [1992] -- 3. History for strategists : British sea power as a relevant past [1994] -- 4. Why strategy is difficult [1999] -- 5. From principles of warfare to principles of war : a Clausewitzian solution [2005] -- 6. Nuclear strategy : the case for a theory of victory [1979] -- 7. The revolution in military affairs [1998] -- 8. Arms control does not control arms [1993] -- 9. Geography and grand strategy [1991] -- 10. Strategic culture as context : the first generation of theory strikes back [1999] -- 11. Force, order, and justice : the ethics of realism in statecraft [1993] -- 12. What is war? : a view from strategic studies [2005].
Includes bibliographical references (pages 190-227) and index.
Keywords: Strategy